2002
DOI: 10.1017/s0033822200064675
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon and Stable Isotope Analyses of Archaeological Bone Consolidated with Hide Glue

Abstract: We tested a simple method for removing a collagen-based glue preservative from bone destined for radiocarbon and stable isotope analyses. The method is sufficient for bone samples from which only stable isotope measurements are required. For 14C dating, such samples of age less than about 10 ka can be adequately dated, but for older samples, the circumstances must be carefully evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 3 publications
2
13
1
Order By: Relevance
“…These findings support previous research which also found no effects of other consolidants or solvents on collagen stable isotope values (Moore et al, 1989;Tuross and Fogel, 1992;Takahashi et al, 2002;France et al, 2011).…”
Section: Average Phosphate Dsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings support previous research which also found no effects of other consolidants or solvents on collagen stable isotope values (Moore et al, 1989;Tuross and Fogel, 1992;Takahashi et al, 2002;France et al, 2011).…”
Section: Average Phosphate Dsupporting
confidence: 92%
“…In general, collagen carbon and nitrogen isotopes appear unaffected by application of consolidants or solvents (Moore et al, 1989;Tuross and Fogel, 1992;Takahashi et al, 2002;France et al, 2011), except in cases where solvents are specifically chosen to remove lipids which tends to enrich carbon isotope values (Hobson et al, 1994;Hilderbrand et al, 1996;Hobson et al, 1997;Burton et al, 2001;Post, 2002). Very few studies have examined effects of consolidants and solvents on hydroxyapatite isotope values.…”
Section: N and Dmentioning
confidence: 99%
“…Some of these works in fact deal with both cleaning techniques and consolidation products at the same time (Fernández Jalvo and Marín Monfort, 2008;Eklund and Thomas, 2010). Study has included articles based on the study of the topography of the surface of the bone (Bromage, 1984;Matienzo and Snow, 1986;Fernández Jalvo and Marín Monfort, 2008) and others based on the study of components of scientific interest extracted from bones, specifically DNA (Eklund and Thomas, 2010), stable isotopes (Moore et al, 1989;Stephan's, 2000;Takahashi and Nelson, 2002) and 14 C (Law et al, 1991;Takahashi and Nelson, 2002). The results show that some conservation techniques and products may interfere with subsequent scientific analyses performed on fossils.…”
Section: Discussion and Future Prospects For Cleaning And Consolidatimentioning
confidence: 99%
“…Some results have also shown that animal glue does not significantly affect the analysis of d 13 C and d 15 N content (Takahashi and Nelson, 2002). Furthermore, in Stephan's (2000) assay on the influence of different consolidants on the analysis of d 18 Ot, he tested two PVAc based consolidants (Mowilith 50 Ò and Ponal Ò ), one cellulose nitrate (Zaponlack) and the natural product shellac and concluded that none of them influence the oxygen analysis.…”
Section: Review Of Experimental Work On the Interference With Subseqmentioning
confidence: 99%
See 1 more Smart Citation